Russlands Bodenkunde in der Welt Eine ost-westliche Transfergeschichte 1880-1945 - Arend, Jan (Vandenhoeck & Ruprecht, 2019)
In the summer of 1914, the Russian agricultural scientist and soil scientist Konstantin Glinka sent a manuscript to Berlin. It contained the first presentation of Russian Soil Science, an early ecology doctrine of the soil, based on black soil research, to a foreign readership. This was the beginning of a success story: the Russian soil science was successful in the interwar period in Europe and the United States. After 1945, she became a classic of modern agricultural and environmental sciences. Jan Arend tells the story of knowledge transfer from east to west. It follows scientists, manuscripts and terms - from the black earth provinces of the Russian Empire to the podiums of international conferences to the cabinets of American agricultural planners and land estimators in Nazi Germany.
Description based on print version record.
KU Open Services
Keywords: History / Europe; History; Electronic books